2018
DOI: 10.1021/acs.energyfuels.8b03260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asphaltene Concentration on the Combustion of a Heavy Fuel Oil Droplet

Abstract: Highlights  Thermogravimetric analysis of heavy fuel oil samples at different asphaltene concentration is discussed.  The influence of high asphaltene concentration on the droplet burning stages is illustrated.  The relation between the droplet ignition delay time and droplet size is discussed at different asphaltene concentration.  The effect of asphaltene concentration on the droplet evolution with time is measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…This result is not answered by either the smaller SMD, shown in Tables 4 and 5, or the slightly slower evaporation of R [36]. Hence, this is a probable root cause of the crust formation on the larger droplets, already observed for HFO [34,35]. The emissions of BL-R, BL-D, and Q15-D cases, shown in Figure 9, are shown in Figure 11.…”
Section: Pollutant Emissionmentioning
confidence: 90%
See 1 more Smart Citation
“…This result is not answered by either the smaller SMD, shown in Tables 4 and 5, or the slightly slower evaporation of R [36]. Hence, this is a probable root cause of the crust formation on the larger droplets, already observed for HFO [34,35]. The emissions of BL-R, BL-D, and Q15-D cases, shown in Figure 9, are shown in Figure 11.…”
Section: Pollutant Emissionmentioning
confidence: 90%
“…The evaporation of heavy fuels is still less known, since the outer surface of the droplet might solidify even for kerosene gel [33]. Significant crust formation was similarly observed for HFO [34], featuring pores on the surface [35] where the oil inside left the droplet when evaporated. To overcome this issue, atomization with steam [30] might help, substituting air with an H 2 O atmosphere in the vicinity of the fuel nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…Further downstream, the temperature again shows a gradual increase. Recently, the TGA analysis on the same HFO sample provided the information that the fuel evaporation occurred in two consecutive steps, where the low boiling gases left out the fuel, while the second phase of the devolatilization occurs at higher temperature [41]. This explained the first flame peak temperature located close to the fuel spray nozzle, which is associated with the first phase of evaporation.…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…Fundamental research on HFO combustion reported in the literature has mostly been carried out using suspended [21][22][23][24][25] and falling droplet [25][26][27][28] techniques, beside numerical modeling [29][30][31][32][33][34][35]. These droplet experiments are unable to reproduce the spray properties seen in combustors, whereas large scale industrial furnaces on the other hand lack the experimental accuracy such that meaningful interpretation of the combustion processes can be made.…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…In the present work, spray combustion of HFO was carried out using a high swirl, turbulent jet flame by using a novel burner design. Due to the high residual content, HFO has a significant quantity of asphaltenes and resins that make it difficult to burn [9,21,42] and this requires longer residence times and higher temperatures for better combustion. The high swirl, turbulent jet flame produced by the burner results in a stabilized flame that can efficiently burn HFO by providing a long residence time and good mixing between fuel and air.…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%